Linguistic Phenomenon: Language Play Among Multilingual Communities on Social Media - Ilmiasari, Nurul; Wijana, I Dewa Putu (CV. Publikasi Indonesia, 2025)
The rapid growth of social media has transformed communication patterns, particularly in multilingual societies where language play (e.g., puns, wordplay) thrives as a creative and humorous form of interaction. Indonesia, with its rich linguistic diversity, serves as an ideal context to study this phenomenon, as social media users frequently blend regional languages, Indonesian, and foreign languages (e.g., English, Korean) to produce engaging and culturally resonant content. Despite its prevalence, research on multilingual language play in digital spaces remains limited, particularly regarding its linguistic mechanisms and sociocultural functions. This research aims to fill this gap by examining the types, techniques, and communicative roles of language games in Indonesian multilingual communities on social media. Using qualitative analysis, this study examines humorous multilingual content from Instagram, TikTok, and YouTube. Through purposive sampling of 100 public examples, it categorizes linguistic techniques and communicative functions, employing thematic and discourse analysis to uncover underlying patterns. The findings show that interlingual puns dominate, primarily using homophony for humor. These serve four key functions: aesthetic (beauty), interpersonal (bonding), cognitive (critical thinking), and ideological (social critique). They demonstrate multilingual speakers’ adaptability in navigating diversity while fostering inclusivity. Such language play transcends entertainment, emerging as a sophisticated tool reinforcing cultural identity, social cohesion, and critical discourse. These findings have implications for sociolinguistic research, digital communication strategies, and language education, suggesting that humor and multilingual creativity can enhance cross-cultural understanding and pedagogical innovation. Future research could explore cross-cultural comparisons or the role of algorithms in shaping linguistic trends on social media.